2016
DOI: 10.1182/asheducation-2016.1.437
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease in mantle cell lymphoma: insights into biology and impact on treatment

Abstract: Despite the recent substantial improvement of clinical outcome in mantle cell lymphoma (MCL), resistance to immunochemotherapy and common relapses are challenges for long-term tumor control. The assessment of minimal residual disease (MRD) by real-time quantitative polymerase chain reaction has emerged as a widely feasible and standardized tool for direct assessment of therapy-induced reduction of tumor burden and regrowth after cytotoxic treatment in MCL, with much improved sensitivity compared with conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…This study demonstrated that rituximab maintenance can improve survival after SCT. MRD assessment in MCL has not been systematically implemented in clinical practice; however, a few studies have shown the critical clinical significance of MRD‐positive disease status and risk of predicting future relapses . Another issue for MRD assessment in MCL is optimization of the technique according to the tissue type used to test MRD, as not all patients have bone marrow involvement at diagnosis and not all patients have peripheral blood lymphocytosis sufficient enough for testing MRD by either flow cytometry or PCR (allele specific quantitative oligonucleotide polymerase chain reaction).…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…This study demonstrated that rituximab maintenance can improve survival after SCT. MRD assessment in MCL has not been systematically implemented in clinical practice; however, a few studies have shown the critical clinical significance of MRD‐positive disease status and risk of predicting future relapses . Another issue for MRD assessment in MCL is optimization of the technique according to the tissue type used to test MRD, as not all patients have bone marrow involvement at diagnosis and not all patients have peripheral blood lymphocytosis sufficient enough for testing MRD by either flow cytometry or PCR (allele specific quantitative oligonucleotide polymerase chain reaction).…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…In recent years, MRD assessment after induction has emerged as an invaluable posttreatment prognostication tool . Despite the fact that most of the so far published studies confirmed predictive significance of achieving MRD negativity after induction, we did not find a single published manuscript in MCL patients that would include MRD assessment in the context of RM therapy only.…”
Section: Discussionmentioning
confidence: 78%
“…Landmark European MCL Network study demonstrated significant survival benefit of RM over observation or interferon alpha . Persistent minimal residual disease (MRD) after induction has been repeatedly associated with imminent clinical relapse and a shorter progression free and overall survival (PFS, OS) . Despite the fact that most of the so far published studies confirmed prognostic significance of MRD after induction, we did not find a single published MCL study that would include RM.…”
Section: Introductionmentioning
confidence: 87%
“…Recurrence of disease is believed to be due to persistence of a relatively small number of lymphoma cells that are below detection level of clinically employed response-evaluation methods. This notion is supported by observations that newer, more sensitive techniques like multicolor flow cytometry (FCM) or polymerase chain reaction (PCR) are able to detect such residual cell population (referred to as minimal residual disease [MRD]) in some NHL patients who are otherwise in CR post completion of therapy [8,9]. MRD cells carry the same phenotypic and genetic markers as the original lymphoma as detected by FCM and PCR.…”
Section: Research Papermentioning
confidence: 93%